Complex systems approaches to the adaptability of human functions and behavior in health, aging, and chronic diseases: protocol for a meta-narrative review - Louis Hognon; Nelly Heraud; Alain Varray; Kjerstin Torre (Systematic Reviews, 2023)
Abstract Background Evaluating the adaptability of human functions and behavior has become a subject of growing interest due to aging populations and the increased prevalence of chronic diseases. Various research traditions, based on complex systems theories, have addressed the adaptability of human functions and behavior. However, despite the different research traditions, no review has so far compared them to provide a reliable and useful synthetic tool. Based on an adapted methodology, study objectives are to refine common and divergent traits in the way adaptability of the human functions and behavior has been studied via complex system approaches, with a special focus on aging and chronic diseases. In order to meet this objective, we will use the methodology of the meta-narrative review, and we present in this article the protocol that we will follow. Methods The meta-narrative review explores the contrasting and complementary ways in which researchers have studied a subject in order to synthesize information and extract theoretical and applied recommendations. In order to carry out this protocol, we detail our methodology of article extraction, coding, and synthesis. We present the six main stages of our review, from the planning stage to the recommendation stage, and the way we will implement the six principles that underpin the construction of a meta-narrative review. Discussion The use of a meta-narrative review methodology will yield greater visibility and comprehension of the adaptability of human functions and behavior studied via complex systems-based approaches. In a broader perspective, this paper is also geared to help future researchers carry out a meta-narrative review by highlighting the main challenges encountered and anticipated as well as elements to be taken into account before starting such a project.